Dhallan dalam Penafsiran Q.S. ad-Dhuha [93]:7 Perspektif Hermeneutika Paul Ricoeur - Rindiani Putri Junieta; Shafwatul Insani (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2026)
Q.S ad-Dhuha [93] is a surah that was revealed to address the Prophet's anxiety because he had not received any revelations from Allah for a long time. Among the eleven verses in Q.S ad-Dhuha, there is one verse that presents a controversial interpretation. The verse describes the Prophet's condition when he was once in a state of misguidance. The confusion surrounding the interpretation of Q.S ad-Dhuha [93]:7 is interesting to explore further in order to obtain the message and meaning contained in the verse. In this paper, the author attempts to explore the meaning using Paul Ricoeur's heuristic method to uncover the symbols contained in the text. The research method used in this paper is a qualitative method with a library-research data collection technique. Through this study, it can be understood that Q.S ad-Dhuha [93]:7 illustrates the evolutionary process of every human being in searching for the path of truth. In the process of searching for these values of truth, humans should not feel satisfied or, conversely, feel hopeless, because Allah is always present to help His servants.